2018
DOI: 10.1139/apnm-2017-0144
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofMentha spicataagainst nicotine-induced toxicity in liver and erythrocytes of Wistar rats

Abstract: The aim of this study was to investigate the protective effect of Mentha spicata supplementation against nicotine-induced oxidative damage in the liver and erythrocytes of Wistar rats. Bioactive substances were determined by liquid chromatography - electrospray ionization - tandem mass spectrometry analysis. Animals were divided into 4 groups of 6 rats each: a normal control group, a nicotine-treated group (1 mg/kg), a group receiving M. spicata extract (100 mg/kg), and a group receiving both M. spicata extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It induces oxidative stress both in vitro and in vivo (Budzynska, Boguszewska‐Czubara, Kruk‐Slomka, Kurzepa, & Biala, ). Moreover, nicotine exposure increases free radicals production (mediators of inflammation) and cooperative lipid peroxidation levels in various tissues (Ben Saad et al, ). Oxidative stress induced by nicotine may play an important role in the pathogenesis of different diseases (Alexandrov et al, ; Hamza & El‐Shenawy, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It induces oxidative stress both in vitro and in vivo (Budzynska, Boguszewska‐Czubara, Kruk‐Slomka, Kurzepa, & Biala, ). Moreover, nicotine exposure increases free radicals production (mediators of inflammation) and cooperative lipid peroxidation levels in various tissues (Ben Saad et al, ). Oxidative stress induced by nicotine may play an important role in the pathogenesis of different diseases (Alexandrov et al, ; Hamza & El‐Shenawy, ).…”
Section: Introductionmentioning
confidence: 99%
“…levels in various tissues (Ben Saad et al, 2018). Oxidative stress induced by nicotine may play an important role in the pathogenesis of different diseases (Alexandrov et al, 2016;Hamza & El-Shenawy, 2017).…”
mentioning
confidence: 99%
“…In spite of the wide advocacy for their use as pesticides, little is currently known about the potentially toxic effects that may arise from their use. The treatment of albino rats with an aqueous solution of nicotine, a compound derived from Nicotiana tabacum, caused oxidative stress and damage to the liver (BenSaad et al, 2018;Chowanski et al, 2016). Recently, we showed that oil extracts of clove, S. aromaticum also caused oxidative stress and liver damage in male Wistar rats (Adeyemi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some plants are abundant in polyphenols that could act as bioactive components to prevent carcinomas and oxidative stress [48,49]. Mentha spicata supplementation protected the liver of Wistar rats against nicotine-induced oxidative damage [50]. Therefore, the ROS-scavenging efficacy of SGV was elevated by kale supplementation and contributed to prevention of cytotoxicity by nicotine.…”
Section: Resultsmentioning
confidence: 99%